Computational characterisation ofToxoplasma gondiiFabG (3-oxoacyl-[acyl-carrier-protein] reductase): a combined virtual screening and all-atom molecular dynamics simulation study - MUTLU, ÖZAL (TAYLOR & FRANCIS INC, 2022)
Toxoplasma gondiiis an opportunistic obligate parasite, ubiquitous around the globe with seropositivity rates that range from 10% to 90% and infection by the parasite of pregnant women causes pre-natal death of the foetus in most cases and severe neurodegenerative syndromes in some. No vaccine is currently available, and since drug-resistance is common amongT. gondiistrains, discovering lead compounds for drug design using diverse tactics is necessary. In this study, the sole constituent isoform of an enzymatic 3-oxoacyl-[acyl-carrier-protein] reduction step in an apicoplast-located fatty acid biosynthesis pathway was chosen as a possible drug target. FASII is prokaryotic therefore, targeting it would pose fewer side-effects to human hosts. After a homology 3D modelling of TgFabG, a high-throughput virtual screening of 9867 compounds, the elimination of ligands was carried out by a flexible ligand molecular docking and 200 ns molecular dynamics simulations, with additional DCCM and PC plot analyses. Molecular Dynamics and related post-MD analyses of the top 3 TgFabG binders selected for optimal free binding energies, showed that L2 maintained strong H-bonds with TgFabG and facilitated structural reorientation expected of FabGs, namely an expansion of the Rossmann Fold and a flexible lid capping. The most flexible TgFabG sites were the alpha 7 helix (the flexible lid region) and the beta 4-alpha 4 and beta 5-alpha 6 loops. For TgFabG-L2, the movements of these regions toward the active site enabled greater ligand stability. Thus, L2 (Skimmine; PubChem ID: 320361), was ultimately selected as the optimal candidate for the discovery of lead compounds for rational drug design. Communicated by Ramaswamy H. Sarma
Keywords: Toxoplasma gondii; 3-oxoacyl-[acyl-carrier-protein] reductase; FabG; structure-based drug design; fatty acid synthesis; FASII; CARRIER PROTEIN REDUCTASE; FATTY-ACID BIOSYNTHESIS; ENOYL-ACP REDUCTASE; TOXOPLASMA-GONDII; PLASMODIUM-FALCIPARUM; DRUG DISCOVERY; APICOPLAST; METABOLISM; SEQUENCE; CHAIN